Novel recommendation for enhancing optical properties of CP-WLEDs by Ba2Si5N8Eu2+ phosphor - Van-Duc Phan; Minh Tran; Q. S. Vu (Institute of Advanced Engineering and Science, 2021)
In this paper, the Ba2Si5N8Eu2+ phosphor is proposed as the novel recommendation for enhancing the optical properties in terms of D-CCT, CRI, CQS, and LO of the CP-WLEDs. Firstly, we conducted the physical model of the CP-WLEDs in the Light Tools software with the main parameters like the real LEDs. Furthermore, the scattering process in LEDs compound of the CP-WLEDs is simulated and investigated by the Matlab software. Then the influence of the Ba2Si5N8Eu2+ concentration on the D-CCT, CRI, CQS, and LO of the CP-WLEDs is investigated. Finally, the research results showed that the Ba2Si5N8Eu2+ concentration has a considerable effect on the D-CCT, CRI, CQS, and LO of the CP-WLEDs. From the results, we can state that the Ba2Si5N8Eu2+ phosphor can be considered as the novel recommendation for enhancing the optical properties of the CP-WLEDs.